Vortex-antivortex dynamics driven by spin-torque in a nanocontact - Zaspel, C.E.; Kireev, V.E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
A spin-polarized current in a nanocontact has been shown to induce the formation of a magnetic vortex at the nanocontact by the Oersted field, and spin-torque drives the vortex core in an elliptical orbit about the nanocontact. For the case of an external in-plane magnetic field in an extended free layer, the magnetization will be uniform far from the nanocontact, implying that vortex formation must be accompanied by the formation of an antivortex. Using the Thiele approach to describe the vortex-antivortex dynamics it is shown that the frequency of gyrotropic motion of the vortex is a function of the nanocontact current which is linear for large vortex-antivortex separations and it becomes nonlinear as the separation is decreased. The equilibrium vortex-antivortex separation can be controlled by the nanocontact current as well as the external magnetic field.